Preparation and therapeutic biological activities of hydrolysate mixture produced from frog (Rana tigrina) skin using protease - Thi Tran, Huyen; Hoang Phan, Anh Thi; Ngoc Nguyen, Tuan Huu; Pham, Son; Minh Nguyen, Nam (Agriculture and Natural Resources, 2025)
Importance of the work: Nowadays, a noncytotoxic hydrolysate containing multiple biological activities is an ideal product for discovering vital bioactive peptides for use in the production of nutraceuticals and pharmaceuticals and for developing alternative treatments for metabolic syndrome. Objectives: To determine the biological activities and bioactive peptides involved in the hydrolysate mixture (HFS) from frog (Rana tigrina) skin. Materials and Methods: The FHS was investigated for its 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging activities, its angiotensin I-converting enzyme (ACE) inhibitory (ACE-I) activity, antimicrobial activities and toxicity to fibroblast (HS 68) cells. Connections of peptides with the ACE in the HFS were determined using high-performance liquid chromatography-tandem mass spectrometry (HPLCMS/MS) and the docking method. Results: The HFS confirmed the DPPH and ABTS scavenging activities. Notably, the HFS inherited ACE-I activity at a significant half-maximal inhibitory concentration value of 85.47 mg/mL but did not involve antimicrobial actions or inhibit the growth of HS 68 cells at contents of 0.5 mg/mL or 10 mg/mL. Four peptides (F1, F2, F3, F4) in the HFS were determined for their amino acid sequences using HPLC-MS/MS. The docking results between these peptides with the ACE model improved insights into the structure-activity relationship of the ACE inhibitory peptides. Notably, F1 contained vital residues for forming the most hydrogen bonds, and a Pi-alkyl interaction resulted in effective ACE-I activity based on its binding energy (-10.9 kcal/mol) compared to captopril (-5.4 kcal/mol). Main finding: All results suggested effective enzymatic hydrolysis had produced HFS containing potential value for its biological activity and non-toxic ability; the novel bioactive peptides found in the HFS could be applied as scaffolds for more intensive research on therapeutic peptides against ACE and contribute to treating hypertension.